Childhood Non-HDL Cholesterol and LDL Cholesterol and Adult Atherosclerotic Cardiovascular Events - Wu, Feitong (United States, 2025)
Background: Although low-density lipoprotein cholesterol (LDL-C) remains the primary cholesterol target in clinical practice in children and adults, non-high-density lipoprotein cholesterol (non-HDL-C) has been suggested as a more accurate measure of atherosclerotic cardiovascular disease (ASCVD) risk. We examined the associations of childhood non-HDL-C and LDL-C levels with adult ASCVD events and determined whether non-HDL-C has better utility than LDL-C in predicting adult ASCVD events.
Methods: This prospective cohort study included 21 126 participants from the i3C Consortium (International Childhood Cardiovascular Cohorts). Proportional hazards regressions were used to estimate the risk for incident fatal and fatal/nonfatal ASCVD events associated with childhood non-HDL-C and LDL-C levels (age- and sex-specific z scores; concordant/discordant categories defined by guideline-recommended cutoffs), adjusted for sex, Black race, cohort, age at and calendar year of child measurement, body mass index, and systolic blood pressure. Predictive utility was determined by the C index.
Results: After an average follow-up of 35 years, 153 fatal ASCVD events occurred in 21 126 participants (mean age at childhood visits, 11.9 years), and 352 fatal/nonfatal ASCVD events occurred in a subset of 11 296 participants who could be evaluated for this outcome. Childhood non-HDL-C and LDL-C levels were each associated with higher risk of fatal and fatal/nonfatal ASCVD events (hazard ratio ranged from 1.27 [95% CI, 1.14-1.41] to 1.35 [95% CI, 1.13-1.60] per unit increase in the risk factor z score). Non-HDL-C had better discriminative utility than LDL-C (difference in C index, 0.0054 [95% CI, 0.0006-0.0102] and 0.0038 [95% CI, 0.0008-0.0068] for fatal and fatal/nonfatal events, respectively). The discordant group with elevated non-HDL-C and normal LDL-C had a higher risk of ASCVD events compared with the concordant group with normal non-HDL-C and LDL-C (fatal events: hazard ratio, 1.90 [95% CI, 0.98-3.70]; fatal/nonfatal events: hazard ratio, 1.94 [95% CI, 1.23-3.06]).
Conclusions: Childhood non-HDL-C and LDL-C levels are associated with ASCVD events in midlife. Non-HDL-C is better than LDL-C in predicting adult ASCVD events, particularly among individuals who had normal LDL-C but elevated non-HDL-C. These findings suggest that both non-HDL-C and LDL-C are useful in identifying children at higher risk of ASCVD events, but non-HDL-C may provide added prognostic information when it is discordantly higher than the corresponding LDL-C and has the practical advantage of being determined without a fasting sample.